La contabilità ambientale regionale Il caso delle regioni Campania, Calabria, Basilicata - SALVI, TANIA (Scuole di dottorato, 2007)
The volume analyses the decision-making process of public entities and defines a regional environmental accounting methodology according to which the environmental variable contributes to the definition of strategic choices. The first part describes the regional public expenditure related to the environmental field and deals with the theoretical and methodological aspects commenting the principles applied to the cases of Campania, Calabria and Basilicata regions through the analysis of the regional financial statements. The second part offers a deep analysis on the relationship between economy and environment through a system of indicators that represent the economic and social context and environmental quality, that is the application of the DPSIR Model (Driving forces-Pressures-States-Impacts-Responses) to the regions examined. From the set of information provided by the analysis of the economic, social and environmental context, public decision-makers can draw an informed judgement on the convenience of specific operations to be planned and implemented.